Analogy interpretation for renewal criminal justice in Indonesia - Anaria, Ulfa (Legality : Jurnal Ilmiah Hukum, 2020)
The order of criminal law in Indonesia until now uses thinking legal-positivism, where the law is considered limited to obeying what is in the text and its meaning which is still formal-textualist. The law must have an element of justice in deciding each case. Thought postivistic legal is considered contrary to the social conditions of society. The times have demanded the law to be adaptive, requiring renewal of criminal law and its implementation in the judiciary. The development of an increasingly sophisticated era raises many new problems in society. This study intends to criticize the prohibition of analogies that are considered to be contrary to the principle of legality. Through normative research methods, researchers try to decipher qualitatively by looking at the theoretical basis of the formulation of the problem made regarding the opinions of experts related to the use of legal analogies. Meanwhile, through a descriptive approach, researchers try to describe the social situation of the people at the time of the prohibition of analogies or the cause of the emergence of the principle of legality with this modern era. The results of this study indicate that a judge is allowed to use analytical interpretation in deciding new cases.